FIQH TANZIL, FIQH WAQI’, DAN FIQH MA’AALAT: Kajian Fiqh pada Strategi Dakwah dalam Ayat-Ayat Jihad - Hayatuddin, Hayatuddin; Jumhadi, Agus Idwar; Khaerudin, Khaerudin; Bamukmin, Novel; Hidayat, Rahmat; Saparudin, Imam (Asosiasi Dosen PTKIS Indonesia, 2025)
This paper examines the integration of Fiqh Tanzil (understanding the divine texts), Fiqh Waqi’ (contextual understanding of reality), and Fiqh Ma’aalat (consideration of consequences) as a strategic framework in Islamic preaching (da'wah), particularly in understanding and conveying jihad verses. The study aims to demonstrate how the combination of these three approaches can provide a comprehensive understanding of jihad verses, adapted to the context of time and place, while maintaining the relevance of da'wah without compromising Islamic principles. Fiqh Tanzil serves as a theological foundation by interpreting primary sources, such as the Qur’an and Hadith, to ensure the authenticity of the message. This approach guarantees that the understanding of jihad verses remains within the framework of authentic Islamic teachings. Fiqh Waqi’ emphasizes the importance of analyzing contemporary social, cultural, and political realities, making da'wah more relevant to the needs and challenges of modern societies. By deeply understanding the conditions of the audience, the message can be delivered contextually and effectively. Meanwhile, Fiqh Ma’aalat evaluates the potential long-term impacts of preaching strategies, ensuring that the conveyed messages create maximum benefit while avoiding risks such as conflicts, misunderstandings, or radicalization. The study employs a case study approach, analyzing specific jihad verses and their application in various da'wah contexts. The findings reveal that this integrative approach is effective in addressing the challenges of modern da'wah, particularly in multicultural and multireligious environments. It also helps communicate Islam as a religion that prioritizes peace, justice, and social harmony. The study concludes by emphasizing the importance of training preachers to master these three approaches. By understanding local and global contexts and considering the social, cultural, and political impacts of their messages, da'wah can become more effective, relevant, and meaningful in contemporary times.